The Struggle of Women to Occupy Parliamentary Seats in the City of Jambi in the 2024 Elections - Dwi P Kusuma; Deshinta C Pertiwi; Rima Rismarwanti; Sutri Destemi Elsi (Penerbit Jurnal Indonesia, 2024)
The struggle of women to occupy parliamentary seats in Jambi City in the 2024 elections is still faced with obstacles such as discrimination and patriarchal culture. Although the 1945 Constitution does not distinguish between men and women, women's representation in the legislature is still low. Efforts such as the 30% quota for women's representation in political parties are expected to increase women's representation. The presence of women in parliament is considered valuable in creating political dynamics and voicing the interests of the people. Factors such as political and social change, personal experience, policy objectives, perceptions of representation, and family support can motivate women to engage in politics. Although there are still challenges, efforts to increase women's representation in politics remain a hope.